Exploring Supply Chain Collaboration in Thai Major Industries - Phong-arjarn, Ekkprawatt; Jeenanunta, Chawalit (Asian Health, Science and Technology Reports, 2012)
Supply chain collaboration (SCC) is increasingly important in organizations, while successful collaboration buildings in Thai industrial supply chains are still limited. This study aims to explore major collaborative activities and major factors that ha ve an influence on the occurrence of SCC in four major industries of Thailand which are Electronics and Computer Industry, Automotive Industry, Textile-Apparel Industry, and Construction Industry. The occurrence of SCC is determined, in terms of, various charac teristics of the firms, which are type of industry, type of company, value of fixed assets, and number of employees. Research data was collected by two approaches; interview and questionnaire. Independent variables list were taken from the SCC factors that most frequently referred in previous studies. Samples of the research were 193 respondent companies from the four industries. Multiv ariate analysis such as Factors Analysis and Logistic Regression were employed for data analysis. The results showed that the major collaborative activity in the industries is the information sharing and the major factors that have an influence on the occurre nces of SCC are top management support as well as trust and good relationship between supply chain partners. This study provides an empirical result that contributes to SCC building which can be used as a guidelines for development of supply chain management in Thailand and in other developing countries as well.